Effect of Sopoongsan on Skin Inflammation and Hyperlocomotion in Socially Isolated Mice with Atopic Dermatitis. (16th September 2022) - Huong Nguyen, Ly Thi; Choi, Min-Jin; Shin, Heung-Mook; Yang, In-Jun
Abstract : Psychological stress is a major exacerbating factor of atopic dermatitis (AD), a chronic inflammatory skin disease. Sopoongsan (SPS), a traditional herbal formula, has been indicated for the treatment of various skin disorders, including AD. This study investigated the effects of SPS on a 2, 4-dinitrochlorobenzene- (DNCB-) induced AD mice model exposed to social isolation (SI) stress. The severity of the AD symptoms and behavioral abnormalities was evaluated. SPS reduced the clinical skin score as evaluated with the SCORing Atopic Dermatitis (SCORAD) index and suppressed the cutaneous infiltration of T-lymphocyte cells, mast cells, and eosinophils in SI-AD mice. The SPS treatment decreased the total distance and mean speed and increased resting time in the open field test (OFT) for these mice. In addition, the time spent in the social zone in the social interaction test also improved when SPS treatment was given. The levels of tumor necrosis factor-alpha (TNF- α ) and interleukin-6 (IL-6) in the prefrontal cortex (PFC) in the SI-AD mice were reduced by the oral administration of SPS. HaCaT and BV2 cells were used for the in vitro experiments. The pretreatment with SPS reduced the protein levels of the thymus and activation-regulated chemokine (TARC) and macrophage-derived chemokine (MDC) in the HaCaT cells stimulated with TNF- α and interferon-gamma (IFN- γ ) (TI). SPS also suppressed TNF- α and IL-6 secretion in lipopolysaccharide- (LPS-) stimulated BV2 cells. These results imply that SPS could be a promising candidate for the treatment of AD in patients under stress conditions and at risk of exacerbation.